2015
DOI: 10.1002/pros.23003
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study shows PTEN deletion is strongly associated with seminal vesicle involvement and extracapsular extension in localized prostate cancer

Abstract: BACKGROUNDLoss of the phosphatase and tensin homolog (PTEN) tumor suppressor gene is a promising marker of aggressive prostate cancer. Active surveillance and watchful waiting are increasingly recommended to patients with small tumors felt to be low risk, highlighting the difficulties of Gleason scoring in this setting. There is an urgent need for predictive biomarkers that can be rapidly deployed to aid in clinical decision-making. Our objectives were to assess the incidence and ability of PTEN alterations to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 44 publications
7
56
0
Order By: Relevance
“…The original assay involved manual staining of slides, but we have now adapted this assay for automated performance on a Ventana autostainer system and demonstrated equivalence to the manual assay. In a subset of 551 tumors for which IHC (by the automated assay) and FISH data were available [22], we found that intact PTEN immunostaining was 91% specific for the absence of PTEN gene deletion by FISH, and 98% and 62% sensitive for detection of homozygous and hemizygous gene deletion, respectively, by FISH [37]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The original assay involved manual staining of slides, but we have now adapted this assay for automated performance on a Ventana autostainer system and demonstrated equivalence to the manual assay. In a subset of 551 tumors for which IHC (by the automated assay) and FISH data were available [22], we found that intact PTEN immunostaining was 91% specific for the absence of PTEN gene deletion by FISH, and 98% and 62% sensitive for detection of homozygous and hemizygous gene deletion, respectively, by FISH [37]. …”
Section: Discussionmentioning
confidence: 99%
“…Since the PTEN gene is almost always lost by deletion in PCa, fluorescence in situ hybridization (FISH) has traditionally been used to detect PTEN loss and examine its association with outcomes [13,14,16,17,21,22]. However, we and others have demonstrated that PTEN loss is commonly subclonal and heterogeneous in primary prostate tumors [2325], making its detection by FISH or techniques that require nucleic acid extraction technically challenging in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…The complete PTEN loss in paraffin embedded PCa specimens in patients with primary PCa was also found to correlate significantly with the presence of high stage disease (T3b-T4) as well as with a Gleason score ≥ 7 [14]. Moreover, as far as it concerns oncologic results after radical prostatectomy, in a multicenter study by Troyer et al PTEN deletion status showed a highly significant correlation with pathologic stage and was also correlated strongly with seminal vesicle invasion, extracapsular extension and higher Gleason scores [15]. In a study by Zu et …”
Section: Editorialmentioning
confidence: 99%
“…The PTEN gene product plays a role in the generation of chemotaxis signals and inhibition of cell proliferation. PTEN deletion can increase progression of prostate carcinoma in mice and human (Wang et al, 2003;Dean et al, 2014;Troyer et al, 2015). In the research conducted by Wan et al, it was indicated that PTEN gene regulates numerous cellular responses on tumour cell chemotaxis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in vitro studies have indicated that the injection of PTEN to mice lacking the gene can reduce metastasis of cancer cells to the lung (Wan et al, 2007). Not only is the dysfunction of PTEN gene associated with several cancers, but also it can lead to cardiovascular diseases, diabetes, Parkinson's disease and schizophrenia (Gori et al, 2009 its mutation is associated with the rapid metastasis and increased tumour invasive power in some tumours (Sakr et al, 2010;Yang et al, 2010;Okutur et al, 2015;Troyer et al, 2015). However, there is a controversy about PTEN role in different cancers.…”
Section: Introductionmentioning
confidence: 99%